AMP-Activated protein kinase phosphorylates cardiac troponin i and alters contractility of murine ventricular myocytes - Oliveira, S; Zhang, Y; Solis, R; Isackson, H; Bellahcene, M; Yavari, A; Pinter, K; Davies, J; Ge, Y; Ashrafian, H; Walker, J; Carling, D; et al. (2012)
Rationale: AMP-activated protein kinase (AMPK) is an important regulator of energy balance and signaling in the heart. Mutations affecting the regulatory γ2 subunit have been shown to cause an essentially cardiac-restricted phenotype of hypertrophy and conduction disease, suggesting a specific role for this subunit in the heart. Objective: The γ isoforms are highly conserved at their C-termini but have unique N-terminal sequences, and we hypothesized that the N-terminus of γ2 may be involved in conferring substrate specificity or in determining intracellular localization. Methods and Results: A yeast 2-hybrid screen of a human heart cDNA library using the N-terminal 273 residues of γ2 as bait identified cardiac troponin I (cTnI) as a putative interactor. In vitro studies showed that cTnI is a good AMPK substrate and that Ser150 is the principal residue phosphorylated. Furthermore, on AMPK activation during ischemia, Ser150 is phosphorylated in whole hearts. Using phosphomimics, measurements of actomyosin ATPase in vitro and force generation in demembraneated trabeculae showed that modification at Ser150 resulted in increased Ca sensitivity of contractile regulation. Treatment of cardiomyocytes with the AMPK activator 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR) resulted in increased myocyte contractility without changing the amplitude of Ca transient and prolonged relaxation despite shortening the time constant of Ca transient decay (tau). Compound C prevented the effect of AICAR on myocyte function. These results suggest that AMPK activation increases myocyte contraction and prolongs relaxation by increasing myofilament Ca sensitivity. Conclusions: We conclude that cTnI phosphorylation by AMPK may represent a novel mechanism of regulation of cardiac function. © 2012 American Heart Association, Inc.